Antioxidant activity of different plant parts extracts of Dracaena umbratica Ridl - Mahmud, Zurina; Yusoff, Zaini; Kamal, Mohd Lias; Jusoff, Kamaruzaman; Kasim, Khairul Farihan (IDOSI Publications, 2010)
Medicinal plants contain phytochemicals which show various significant biological and pharmacological activities. In this study, the hexane, dichloromethane and methanol extracts from different parts (leaves, rhizomes and roots) of a local medicinal plant, Dracena umbratica, Ridl (Agavaceae) were evaluated for antioxidative activity using ferric thiocyanate (FTC) method and also DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging assay. The results showed that all the extracts exhibited weak radical scavenging activity and differ significantly from the standard antioxidants which are vitamin C and butylated hydroxytoluene (BHT). However results from the ferric thiocyanate (FTC) method showed that all the extracts except that of hexane and dichloromethane extracts of the rhizome of this plant possess high antioxidative property which was comparable to the standard reference, BHT. The antioxidative activity of these extracts did not differ significantly (P<0.5) from BHT. These results suggest that this plant species may have low content of radical scavenging compounds but can still be developed as potential antioxidant.